Carbohydrates concentration in leaves of potato plants affected by nitrogen fertilization rates - Fontes, Paulo Cezar Rezende; Silva, Tania Pires da; Finger, Fernando Luiz; Cecon, Paulo Roberto; Ferreira, Ana Paula Sato; Braun, Heder (Revista Ceres, 2016)
At poor conditions of nitrogen (N) in the soil, potato plants may accumulate starch in leaves and be indicative of N nutritional stress. The objective of this work was to determine the effects of N rates (0, 50, 100, 200 and 300 kg ha -1 of N) on the concentrations of carbohydrates (total soluble sugars-TSS, reducing sugars-RS, non-reducing sugars-NRS and starch) in the fourth leaf (FL) of two potato cultivars (Asterix and Atlantic) and their critical levels (CL) associated to the N fertilization rate necessary to obtain the maximum physical (MPE) and economic (MEE) efficiency of tubers. A randomized block design with four replications was used in both experiments. On day 21 after plant emergence, four FL were collected from four plants. Potatoes plants fertilized with low rates of N accumulated less TSS in leaves than those properly fertilized. The opposite occurred with content of starch. The cultivars showed similar responses to five doses of N in relation to contents of starch and TSS. However, the response to the increase in doses of N for RS, NRS and Starch/NRS is cultivar-specific. The correlations between contents of RS, NRS and Starch/NRS with the starch and TSS were dependent on the potato cultivar.

Em condições de deficiência de nitrogênio (N) no solo, as plantas de batata podem acumular amido nas folhas e ser indicativo de estresse nutricional de N. Determinou-se o efeito de doses de N (0; 50; 100; 200 e 300 kg ha -1 ) sobre os teores de carboidratos (açúcares solúveis totais-AST, açúcares redutores-AR e não redutores-ANR e amido) produzidos na quarta folha (QF) de dois cultivares de batata (Asterix e Atlantic) e seus níveis críticos (NC) associados à dose de N necessária à obtenção da máxima eficiência física (MEF) e econômica (MEE) de tubérculos. Em ambos os experimentos foi utilizado o delineamento em blocos casualizados, com quatro repetições. Aos 21 dias, após a emergência das plantas, foram coletadas quatro QF de quatro plantas. Plantas de batatas que receberam as menores doses de N acumularam menos AST nas folhas do que aquelas adequadamente nutridas. O oposto ocorreu com o teor de amido. As cultivares apresentaram respostas similares para as cinco doses de N quanto aos teores de amido e AST. Entretanto, é cultivar específica a reposta ao incremento na dose de N para AR, ANR e Amido/ANR. As correlações entre os teores de AR, ANR e Amido/ANR com os teores de amido e de AST são dependentes do cultivar de batata.
Keywords: Correlation; Fourth leaf; Solanum tuberosum L.; Sugar; Starch